1995
DOI: 10.1111/j.1365-2222.1995.tb00008.x
|View full text |Cite
|
Sign up to set email alerts
|

The differential release of eosinophil granule proteins. Studies on patients with acute bacterial and viral infections

Abstract: It is concluded that eosinophils are activated during acute bacterial infections and that this activation results in the preferential mobilisation of ECP. The simultaneous assay of the two eosinophil proteins, ECP and EPO, may give new insight into the role of the eosinophil in disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 18 publications
2
42
0
Order By: Relevance
“…Since EDN levels began to rise coincident with the peak of eosinophilia, it seems likely that the source was the newly recruited eosinophils or immature cells still developing in the bone marrow. Although the differential secretion of EDN and MBP has not been noted previously, there is precedence for the differential secretion of eosinophil granule proteins in bacterial and viral infections (19). EDN levels measured in other parasitic diseases seem to correlate with the number of peripheral blood eosinophils (38).…”
Section: Discussionmentioning
confidence: 97%
“…Since EDN levels began to rise coincident with the peak of eosinophilia, it seems likely that the source was the newly recruited eosinophils or immature cells still developing in the bone marrow. Although the differential secretion of EDN and MBP has not been noted previously, there is precedence for the differential secretion of eosinophil granule proteins in bacterial and viral infections (19). EDN levels measured in other parasitic diseases seem to correlate with the number of peripheral blood eosinophils (38).…”
Section: Discussionmentioning
confidence: 97%
“…The serum concentration of ECP and EPX were assayed by using radioimmunoassays (Pharmacia Diagnostics AB, Uppsala, Sweden) and of EPO by means of a specific fluorescence enzyme immunoassay (FEIA) (Karawajczyk et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Together with the well-documented involvement of eosinophils in parasitic infection, ECP levels are also increased in viral (Kristjansson et al , 2005 ) and bacterial infection (Venge et al , 1978 ;Karawajczyk et al , 1995 ;Niehaus et al , 2000 ;Ashitani et al , 2003 ), and a specifi c eosinophil activation is reported in bacterial infection (Kvarnhammar and Cardell , 2012 ). Although the direct contribution of eosinophils in bacterial infection is not so well established, many references in the literature indicate that this cell type complements signifi cantly the neutrophil ' s role during host defence.…”
Section: The Eosinophil Cationic Protein (Ecp) In Host Defencementioning
confidence: 96%